The UK National Arts Education Archive: Ideas and Imaginings. (June 2017) - Adams, Jeff; Bailey, Rowan; Walton, Neil
Abstract: The National Arts Education Archive (NAEA) is housed and maintained by the Yorkshire Sculpture Park (YSP), and managed by YSP coordinators and educators with a well‐established volunteer programme. This year, 2017, as part of the celebrations of the YSP's 40th anniversary, the Archive will hold its own exhibition entitled Treasures Revealed : a collection of items selected by people who have been involved in the Archive, whether as donors, volunteers, researchers, artists, trustees or steering group members. In parallel with the exhibition, this article aims to give voice to a selection of individuals and groups associated with the Archive, discussing their interests and experiences of it, and their thoughts on its value and importance as a repository of arts education materials, ideals and practices. Our primary motivations were to consider these different voices in relation to the purpose, direction and relevance of the NAEA today. These exchanges raise fundamental questions and debates about what art education is and what it might become, and how these historical collections, and creative engagements with it, might help to shape our contemporary thinking.